Weather, habitat composition, and female behavior interact to modify offspring survival in Greater Sage‐Grouse. Issue 1 (January 2017) - Gibson, Daniel; Blomberg, Erik J.; Atamian, Michael T.; Sedinger, James S.
Abstract: Weather is a source of environmental variation that can affect population vital rates. However, the influence of weather on individual fitness is spatially heterogeneous and can be driven by other environmental factors, such as habitat composition. Therefore, individuals can experience reduced fitness (e.g., decreased reproductive success) during poor environmental conditions through poor decisions regarding habitat selection. This requires, however, that habitat selection is adaptive and that the organism can correctly interpret the environmental cues to modify habitat use. Greater Sage‐Grouse ( Centrocercus urophasianus ) are an obligate of the sagebrush ecosystems of western North America, relying on sagebrush for food and cover. Greater Sage‐Grouse chicks, however, require foods with high nutrient content (i.e., forbs and insects), the abundance of which is both temporally and spatially dynamic and related primarily to water availability. Our goal was to assess whether nest site selection and movements of broods by females reduced the negative effect of drought on offspring survival. As predicted, chick survival was negatively influenced by drought severity. We found that sage‐grouse females generally preferred to nest and raise their young in locations where their chicks would experience higher survival. We also found that use of habitats positively associated with chick survival were also positively associated with drought severity, which suggests that females reduced drought impacts on their dependent young by selecting more favorable environments during drought years. Although our findings suggest that female nest site selection and brood movement rates can reduce the negative effects of drought on early offspring survival, the influence of severe drought conditions was not completely mitigated by female behavior, and that drought conditions should be considered a threat to Greater Sage‐Grouse population persistence.